2007
DOI: 10.1080/13803390600659376
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activation during word processing in late bilinguals: Similarities and differences as revealed by functional magnetic resonance imaging

Abstract: Functional magnetic resonance imaging was used to compare cortical organization of the first (L1, Russian) and second (L2, English) languages. Six fluent Russian-English bilinguals who acquired their second language postpuberty were tested with words and nonwords presented either auditorily or visually. Results showed that both languages activated similar cortical networks, including the inferior frontal, middle frontal, superior temporal, middle temporal, angular, and supramarginal gyri. Within the inferior f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 76 publications
0
21
0
1
Order By: Relevance
“…Thus, all bilinguals had a perfect command of both languages at all levels and self-reported the need for making continuous changes between Spanish and Catalan depending on the interlocutor present. Noteworthy, subjective measures of self-reported language proficiency appear to provide an effective measure of bilingual ability [16] (Marian et al 2007). This is probably even more so for very homogeneous samples like the one tested in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, all bilinguals had a perfect command of both languages at all levels and self-reported the need for making continuous changes between Spanish and Catalan depending on the interlocutor present. Noteworthy, subjective measures of self-reported language proficiency appear to provide an effective measure of bilingual ability [16] (Marian et al 2007). This is probably even more so for very homogeneous samples like the one tested in this study.…”
Section: Methodsmentioning
confidence: 99%
“…In general, these studies have found that when the degree of proficiency for both languages in bilinguals is very high, a common language system comprising the left hemisphere language network appears to be responsible for the processing of both languages (e.g., Chee et al, 2003;Hasegawa, Carpenter, & Just, 2002;Hernandez, Hofmann, & Kotz, 2007;Klein, Watkins, Zatorre, & Milner, 2006;Perani et al, 1998). In bilinguals who are more proficient in one language than the other, however, a more extended network of activations is observed for the weaker language that includes brain regions related to speech motor and cognitive functions (e.g., Golestani et al, 2006;Kovelman, Baker, & Petitto, 2008;Luke, Liu, Wai, Wan, & Tan, 2002;Marian et al, 2007;Pillai et al, 2003;Tham et al, 2005;Yokoyama et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…In a report on L2 lexical decision, Marian et al (2007), Marian, Spivey, and Hirschc (2003) found that proficient L2 learners activated the posterior and superior regions of the left temporal lobe. However, in the case of non-proficient L2 learners, it is still unclear whether they use the left middle temporal gyrus during L2 lexical decision, since there has been no neuroimaging study which has examined this specific issue.…”
Section: Introductionmentioning
confidence: 98%